Porous bipolar composite current collector for improving rate capability of battery and preparation method of porous bipolar composite current collector

By designing a porous bipolar composite current collector and utilizing a base membrane structure of microporous polymer layers and nanoscale pores, the problem of Li+ diffusion limitation in lithium-ion batteries has been solved, and the rate performance and stability of the battery have been significantly improved.

CN119340398APending Publication Date: 2025-01-21JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411688386.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing composite liquid collectors have Li+ diffusion limitation problems in lithium-ion batteries, resulting in uneven distribution of Li+, affecting the battery's rate performance and capacity stability.

Method used

Designed a multi -porous bipolar composite fluid, which consists of a positive metal layer, micropore polymer layer, base film, micropore polymer layer, and negative metal layer. Force, the base membrane and micropore polymer layer of the nano -level pores are formed to shorten the transmission path of li+.

Benefits of technology

It significantly improves the rate performance and stability of the battery, reduces the number of components, simplifies the battery structure, and improves the overall performance of the battery without reducing the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340398A_ABST
    Figure CN119340398A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a porous bipolar composite current collector for improving the rate capability of a battery and a preparation method. The porous bipolar composite current collector prepared by the invention comprises a positive electrode metal layer, a microporous polymer layer, a base membrane, a microporous polymer layer and a negative electrode metal layer. The porous bipolar composite current collector prepared by the invention can greatly shorten the transmission path of Li < + >, so that the porous bipolar composite current collector has excellent battery rate capability and has a wide application prospect in the technical field of lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a porous bipolar composite current collector and a preparation method thereof for improving the rate performance of a battery. Background Art

[0002] As a new type of battery current collector material, composite current collector has broad application prospects and huge market potential in the fields of lithium-ion batteries and so on. Composite current collector is a new type of battery current collector material, which is made by compounding polymer materials and metals to achieve functions such as conductivity, support and protection. The typical structure of the composite current collector is a sandwich structure of "metal conductive layer-polymer material support layer-metal conductive layer". The polymer material in the inner layer provides good support and protection, while the metal conductive layers on both sides are responsible for the conduction of current. With the continuous expansion of the new energy vehicle market and the continuous improvement of consumers' requirements for battery performance, traditional current collectors have been unable to meet market demand. Although the composite current collector has improved battery performance to a certain extent, Li + The diffusion limitation problem in batteries remains unsolved. The main problem is that Li + The uneven distribution increases with the thickness of the electrode. This uneven electrochemical process in the battery may cause damage to the active particles and interfaces, resulting in poor rate performance of the battery and even irreversible capacity decay. In order to solve the problem of lithium ion diffusion limitation and further improve the battery rate performance while ensuring the battery energy density, it is necessary to start from the internal pores of the composite current collector and construct a structure that can shorten the Li + Porous bipolar composite current collectors for transport paths.

[0003] In order to overcome the defects of the prior art, the present invention provides a porous bipolar composite current collector and a preparation method for improving the rate performance of a battery. Summary of the invention

[0004] The purpose of the present invention is to provide a porous bipolar composite current collector and a preparation method for improving battery rate performance, so as to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The porous bipolar composite current collector used to improve the battery rate performance comprises, from top to bottom, a positive electrode metal layer, a microporous polymer layer, a base film, a microporous polymer layer, and a negative electrode metal layer; the microporous polymer layer is microporous polyimide or microporous polyvinylidene fluoride-hexafluoropropylene copolymer.

[0007] More optimally, the base film is any one of aromatic polyamide fiber, polyimide, polypropylene, and polytetrafluoroethylene.

[0008] More optimally, the base film is required to have a nano-scale porosity of 60-65%, an average pore size of 0.3-0.5 microns, and a thickness of 15 microns.

[0009] More optimally, the base film is aromatic polyamide fiber.

[0010] More optimally, the microporous polymer layer has a thickness of 4.0-4.5 microns; the positive electrode metal layer is an aluminum layer with a thickness of 1.0-1.5 microns; and the negative electrode metal layer is a copper layer with a thickness of 1.0-1.5 microns.

[0011] A method for preparing a porous bipolar composite current collector for improving battery rate performance comprises the following steps:

[0012] Step 1: dissolving polyvinylidene fluoride-hexafluoropropylene copolymer in acetone solution, and then slowly adding deionized water to dilute it to obtain a slurry;

[0013] Step 2: coating the slurry on both sides of the aromatic polyamide fiber base layer, forming a microporous structure after the solvent evaporates, and vacuum drying to obtain a microporous polymer layer;

[0014] Step 3: Pre-treat both sides of the base layer with the microporous polymer layer with oxygen plasma, and then deposit copper layers and aluminum layers on both sides respectively by magnetron sputtering process to obtain a porous bipolar composite current collector for improving the battery rate performance.

[0015] More optimally, in step 1, the concentration of the acetone solution is 10-15%; and the amount of deionized water added is 10-15wt%.

[0016] More optimally, in step 2, the microporous structure is formed after the solvent evaporates: the rapid evaporation of the acetone and water mixture can promote the phase separation of the polyvinylidene fluoride-hexafluoropropylene copolymer, thereby forming a microporous structure, wherein the pore size can be adjusted by controlling the amount of water added.

[0017] Preferably, in step 3, oxygen plasma is used to pre-treat both sides of the substrate to enhance the bonding force between the porous polymer and the metal; the magnetron sputtering pressure is less than 10 -5 Argon is used as the protective gas; oxygen plasma treatment parameters: at room temperature, the oxygen flow rate is set to 30-35sccm, the power is set to 50-60W, the pressure is set to 0.2-0.3Torr, and the treatment time is 60-70s.

[0018] Beneficial effects of the present invention:

[0019] The porous bipolar composite current collector prepared by the present invention comprises a positive electrode metal layer, a microporous polymer layer, a base film, a microporous polymer layer and a negative electrode metal layer. The present invention has the following technical advantages:

[0020] (1) The present invention can effectively improve the bonding force between the metal and the porous polymer and enhance the stability of the porous composite current collector during the battery cycle by treating the surface of the porous polymer with oxygen plasma.

[0021] (2) Compared with ordinary bipolar current collectors, the present invention has many advantages. First, it reduces the number of components, simplifies the battery structure, and improves the battery energy density. Furthermore, its unique positive and negative porous metal layers are combined with a nanoporous base layer with stable physical and chemical properties, making the Li + can pass through the current collector, thus significantly shortening the Li + This design greatly improves the rate performance of the battery without reducing the battery energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0023] Figure 1 Schematic diagram of the porous bipolar composite current collector structure of the present invention;

[0024] Among them, 1: positive electrode metal layer + microporous polymer layer; 2: base film; 3: negative electrode metal layer + microporous polymer layer. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Source of raw materials:

[0027] Polyvinylidene fluoride-hexafluoropropylene copolymer, molecular weight 455000; aromatic polyamide fiber base layer, model Kevlar 49.

[0028] Example 1: Step 1: dissolving polyvinylidene fluoride-hexafluoropropylene copolymer in a 10% acetone solution, and then slowly adding 10% deionized water to dilute it to obtain a slurry;

[0029] Step 2: coating the slurry on both sides of the aromatic polyamide fiber substrate, forming a microporous structure after the solvent evaporates, and vacuum drying to obtain a microporous polymer layer; wherein the aromatic polyamide fiber substrate has a nano-scale porosity of 60%, an average pore diameter of 0.4 microns, and a thickness of 15 microns; and the microporous polymer layer has a thickness of 4 microns;

[0030] Step 3: Pre-treat both sides of the substrate with the microporous polymer layer with oxygen plasma, and then deposit copper and aluminum layers on both sides by magnetron sputtering to obtain a porous bipolar composite current collector for improving the battery rate performance; the copper layer thickness is 1.5 microns, the aluminum layer thickness is 1.5 microns; the magnetron sputtering pressure is 10 -6 Argon was used as the protective gas; oxygen plasma treatment process: at room temperature, the oxygen flow rate was set to 30 sccm, the power was set to 50 W, the pressure was set to 0.2 Torr, and the treatment time was 60 s.

[0031] Example 2: The thickness of the positive electrode aluminum layer is 1 micron, and the thickness of the negative electrode copper layer is 1 micron

[0032] Step 1: dissolving polyvinylidene fluoride-hexafluoropropylene copolymer in a 10% acetone solution, and then slowly adding 10% deionized water to dilute it to obtain a slurry;

[0033] Step 2: coating the slurry on both sides of the aromatic polyamide fiber substrate, forming a microporous structure after the solvent evaporates, and vacuum drying to obtain a microporous polymer layer; wherein the aromatic polyamide fiber substrate has a nano-scale porosity of 60%, an average pore diameter of 0.4 microns, and a thickness of 15 microns; and the microporous polymer layer has a thickness of 4 microns;

[0034] Step 3: Pre-treat both sides of the substrate with the microporous polymer layer with oxygen plasma, and then deposit copper and aluminum layers on both sides by magnetron sputtering to obtain a porous bipolar composite current collector for improving the battery rate performance; the copper layer thickness is 1 micron, the aluminum layer thickness is 1 micron; the magnetron sputtering pressure is 10 -6 Argon was used as the protective gas; oxygen plasma treatment process: at room temperature, the oxygen flow rate was set to 30 sccm, the power was set to 50 W, the pressure was set to 0.2 Torr, and the treatment time was 60 s.

[0035] Example 3: The thickness of the positive electrode aluminum layer is 1.3 microns, and the thickness of the negative electrode copper layer is 1.3 microns

[0036] Step 1: dissolving polyvinylidene fluoride-hexafluoropropylene copolymer in a 10% acetone solution, and then slowly adding 10% deionized water to dilute it to obtain a slurry;

[0037] Step 2: coating the slurry on both sides of the aromatic polyamide fiber substrate, forming a microporous structure after the solvent evaporates, and vacuum drying to obtain a microporous polymer layer; wherein the aromatic polyamide fiber substrate has a nano-scale porosity of 60%, an average pore diameter of 0.4 microns, and a thickness of 15 microns; and the microporous polymer layer has a thickness of 4 microns;

[0038] Step 3: Pre-treat both sides of the substrate with the microporous polymer layer with oxygen plasma, and then deposit copper and aluminum layers on both sides by magnetron sputtering to obtain a porous bipolar composite current collector for improving the battery rate performance; the copper layer thickness is 1.3 microns, the aluminum layer thickness is 1.3 microns; the magnetron sputtering pressure is 10 -6 Argon was used as the protective gas; oxygen plasma treatment process: at room temperature, the oxygen flow rate was set to 30 sccm, the power was set to 50 W, the pressure was set to 0.2 Torr, and the treatment time was 60 s.

[0039] Example 4: Microporous polymer layer thickness is 4.3 microns

[0040] Step 1: dissolving polyvinylidene fluoride-hexafluoropropylene copolymer in a 10% acetone solution, and then slowly adding 10% deionized water to dilute it to obtain a slurry;

[0041] Step 2: coating the slurry on both sides of the aromatic polyamide fiber substrate, forming a microporous structure after the solvent evaporates, and vacuum drying to obtain a microporous polymer layer; wherein the aromatic polyamide fiber substrate has a nano-scale porosity of 60%, an average pore diameter of 0.4 microns, and a thickness of 15 microns; and the microporous polymer layer has a thickness of 4.3 microns;

[0042] Step 3: Pre-treat both sides of the substrate with the microporous polymer layer with oxygen plasma, and then deposit copper and aluminum layers on both sides by magnetron sputtering to obtain a porous bipolar composite current collector for improving the battery rate performance; the copper layer thickness is 1.5 microns, the aluminum layer thickness is 1.5 microns; the magnetron sputtering pressure is 10 -6 Argon was used as the protective gas; oxygen plasma treatment process: at room temperature, the oxygen flow rate was set to 30 sccm, the power was set to 50 W, the pressure was set to 0.2 Torr, and the treatment time was 60 s.

[0043] Example 5: Microporous polymer layer thickness is 4.5 microns

[0044] Step 1: dissolving polyvinylidene fluoride-hexafluoropropylene copolymer in a 10% acetone solution, and then slowly adding 10% deionized water to dilute it to obtain a slurry;

[0045] Step 2: coating the slurry on both sides of the aromatic polyamide fiber substrate, forming a microporous structure after the solvent evaporates, and vacuum drying to obtain a microporous polymer layer; wherein the aromatic polyamide fiber substrate has a nano-scale porosity of 60%, an average pore diameter of 0.4 microns, and a thickness of 15 microns; and the microporous polymer layer has a thickness of 4.5 microns;

[0046] Step 3: Pre-treat both sides of the substrate with the microporous polymer layer with oxygen plasma, and then deposit copper and aluminum layers on both sides by magnetron sputtering to obtain a porous bipolar composite current collector for improving the battery rate performance; the copper layer thickness is 1.5 microns, the aluminum layer thickness is 1.5 microns; the magnetron sputtering pressure is 10 -6 Argon was used as the protective gas; oxygen plasma treatment process: at room temperature, the oxygen flow rate was set to 30 sccm, the power was set to 50 W, the pressure was set to 0.2 Torr, and the treatment time was 60 s.

[0047] Example 6: The thickness of the positive electrode aluminum layer is 1 micron, the thickness of the negative electrode copper layer is 1 micron, and the thickness of the microporous polymer layer is 4.5 microns

[0048] Step 1: dissolving polyvinylidene fluoride-hexafluoropropylene copolymer in a 10% acetone solution, and then slowly adding 10% deionized water to dilute it to obtain a slurry;

[0049] Step 2: coating the slurry on both sides of the aromatic polyamide fiber substrate, forming a microporous structure after the solvent evaporates, and vacuum drying to obtain a microporous polymer layer; wherein the aromatic polyamide fiber substrate has a nano-scale porosity of 60%, an average pore diameter of 0.4 microns, and a thickness of 15 microns; and the microporous polymer layer has a thickness of 4.5 microns;

[0050] Step 3: Pre-treat both sides of the substrate with the microporous polymer layer with oxygen plasma, and then deposit copper and aluminum layers on both sides by magnetron sputtering to obtain a porous bipolar composite current collector for improving the battery rate performance; the copper layer thickness is 1 micron, the aluminum layer thickness is 1 micron; the magnetron sputtering pressure is 10 -6 Argon was used as the protective gas; oxygen plasma treatment process: at room temperature, the oxygen flow rate was set to 30 sccm, the power was set to 50 W, the pressure was set to 0.2 Torr, and the treatment time was 60 s.

[0051] Comparative Example 1: The microporous polymer layer is removed, and a positive electrode aluminum layer with a thickness of 1.5 microns and a negative electrode copper layer with a thickness of 1.5 microns are directly magnetron sputtered on the aromatic polyamide fiber substrate. The rest is the same as Example 1, and the specific steps are as follows: Step 1: Oxygen plasma is pretreated on both sides of the aromatic polyamide fiber substrate, and then a copper layer and an aluminum layer are deposited on both sides by a magnetron sputtering process to obtain a porous bipolar composite current collector for improving the battery rate performance; wherein the copper layer has a thickness of 1.5 microns and the aluminum layer has a thickness of 1.5 microns; the magnetron sputtering gas pressure is 10 -6 Argon was used as the protective gas; oxygen plasma treatment process: at room temperature, the oxygen flow rate was set to 30 sccm, the power was set to 50 W, the pressure was set to 0.2 Torr, and the treatment time was 60 s.

[0052] Comparative Example 2: After coating the microporous polymer layer, without using oxygen plasma treatment, a positive electrode aluminum layer with a thickness of 1.5 microns and a negative electrode copper layer with a thickness of 1.5 microns were directly magnetron sputtered on the aromatic polyamide fiber base layer. The rest was the same as Example 1, and the specific steps were as follows: Step 1: Dissolve the polyvinylidene fluoride-hexafluoropropylene copolymer in a 10% acetone solution, and then slowly add 10% deionized water to dilute it to obtain a slurry;

[0053] Step 2: coating the slurry on both sides of the aromatic polyamide fiber substrate, forming a microporous structure after the solvent evaporates, and vacuum drying to obtain a microporous polymer layer; wherein the aromatic polyamide fiber substrate has a nano-scale porosity of 60%, an average pore diameter of 0.4 microns, and a thickness of 15 microns; and the microporous polymer layer has a thickness of 4 microns;

[0054] Step 3: Copper layer and aluminum layer are deposited on both sides of the base layer with microporous polymer layer by magnetron sputtering process to obtain porous bipolar composite current collector for improving battery rate performance; wherein the thickness of copper layer is 1.5 microns, the thickness of aluminum layer is 1.5 microns; the pressure of magnetron sputtering is 10 -6 , and argon was used as the protective gas.

[0055] Detection test:

[0056] Rate test: The porous bipolar composite current collectors obtained in Examples 1-6 and Comparative Examples 1-2 were simulated and applied in a 10Ah ternary lithium battery, and a 4C rate test was performed starting from SOC 0. The results are shown in the following table:

[0057] 4C charging 15 minutes SOC Example 1 76.8% Example 2 74.1% Example 3 75.5% Example 4 74.5% Example 5 73.3% Example 6 70.6% Comparative Example 1 53.5% Comparative Example 2 67.3%

[0058] Conclusion: According to the test results, the porous bipolar current collector prepared in the embodiment of the present invention is significantly better than the comparative example 1 in terms of rate performance. This is mainly due to its innovative structural design, that is, by combining the positive and negative porous metal layers with the nanoporous base layer with stable physical and chemical properties, it effectively promotes the Li + The penetration transmission during the charge and discharge process significantly shortens its transmission path, thereby showing excellent rate performance in secondary battery applications. In addition, a comparative analysis of the embodiment and comparative example 2 shows that oxygen plasma treatment on the surface of the porous polymer can significantly improve the interfacial bonding force between the metal and the porous polymer, thereby further enhancing the rate performance of the porous composite current collector during the battery cycle.

[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0060] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A porous bipolar composite current collector for improving battery rate performance, characterized in that: From top to bottom, they are positive electrode metal layer, microporous polymer layer, base film, microporous polymer layer and negative electrode metal layer; the microporous polymer layer is microporous polyimide or microporous polyvinylidene fluoride-hexafluoropropylene copolymer.

2. The porous bipolar composite current collector for improving battery rate performance according to claim 1, characterized in that: The base film is any one of aromatic polyamide fiber, polyimide, polypropylene and polytetrafluoroethylene.

3. The porous bipolar composite current collector for improving battery rate performance according to claim 2, characterized in that: The base film is required to have a nano-scale porosity of 60-65%, an average pore size of 0.3-0.5 microns, and a thickness of 15 microns.

4. The porous bipolar composite current collector for improving battery rate performance according to claim 2, characterized in that: The base film is aromatic polyamide fiber.

5. The porous bipolar composite current collector for improving battery rate performance according to claim 1, characterized in that: The microporous polymer layer has a thickness of 4.0-4.5 microns; the positive electrode metal layer is an aluminum layer with a thickness of 1.0-1.5 microns; and the negative electrode metal layer is a copper layer with a thickness of 1.0-1.5 microns.

6. A method for preparing a porous bipolar composite current collector for improving battery rate performance, characterized in that: The following steps are involved: Step 1: dissolving polyvinylidene fluoride-hexafluoropropylene copolymer in acetone solution, and then slowly adding deionized water to dilute it to obtain a slurry; Step 2: coating the slurry on both sides of the aromatic polyamide fiber base layer, forming a microporous structure after the solvent evaporates, and vacuum drying to obtain a microporous polymer layer; Step 3: Pre-treat both sides of the base layer with the microporous polymer layer with oxygen plasma, and then deposit copper layers and aluminum layers on both sides respectively by magnetron sputtering process to obtain a porous bipolar composite current collector for improving the battery rate performance.

7. The method for preparing a porous bipolar composite current collector for improving battery rate performance according to claim 6, characterized in that: In step 1, the concentration of the acetone solution is 10-15%; the amount of deionized water added is 10-15wt%.

8. The method for preparing a porous bipolar composite current collector for improving battery rate performance according to claim 6, characterized in that: In step 3, the magnetron sputtering gas pressure is less than 10 -5 , and argon is used as a protective gas; the thickness of the magnetron sputtering copper layer is 1.0-1.5 microns, and the thickness of the magnetron sputtering aluminum layer is 1.0-1.5 microns; oxygen plasma treatment parameters: at room temperature, the oxygen flow rate is set to 30-35sccm, the power is set to 50-60W, the pressure is set to 0.2-0.3Torr, and the treatment time is 60-70s.

9. Use of the porous bipolar composite current collector for improving battery rate performance according to any one of claims 1 to 5 in a lithium ion battery.

Citation Information

Cited By

  • Composite current collector with elastically deformable thickness, preparation method of composite current collector and lithium ion battery

    CN120824360A

  • Composite current collector with thickness capable of elastic deformation, preparation method thereof and lithium ion battery

    CN120824360B